Assessing the Impacts of Climate Variability on Fertilizer Management Decisions for Reducing Nitrogen Losses from Corn Silage Production. Issue 4 (1st July 2019) - Smith, Ward; Grant, Brian; Qi, Zhiming; He, Wentian; VanderZaag, Andrew; Drury, Craig F.; Vergè, Xavier; Balde, Hambaliou; Gordon, Robert; Helmers, Mathew J.
Abstract : There is an incentive for dairy farmers to maximize crop production while minimizing costs and environmental impacts. In cold climates, farmers have limited opportunity to balance field activities and manure storage requirements while limiting nutrient losses. A revised DeNitrification DeComposition (DNDC) model for simulating tile drainage was used to investigate fertilizer scenarios when applying dairy slurry or urea on silage corn ( Zea mays L.) to examine N losses over a multidecadal horizon at locations in eastern Canada and the US Midwest. Management scenarios included timing (spring, fall, split, and sidedress) and method of application (injected [10 cm], incorporated [5 cm], and broadcast). Reactive N losses (NO3 − from drainage and runoff, N2 O, and NH3 ) were greatest from broadcast, followed by incorporated and then injected applications. Among the fertilizer timing scenarios, fall manure application resulted in the greatest N loss, primarily due to increased N leaching in non‐growing‐season periods, with 58% more N loss per metric ton of silage than spring application. Split and sidedress mineral fertilizer had the lowest N losses, with average reductions of 9.5 and 4.9%, respectively, relative to a single application. Split application mitigated losses more so than sidedress by reducing the soil pH shift due to urea hydrolysis and NH3 volatilization during the warmer June period. This assessment helps to distinguish which fertilizer practices are more effective in reducing N loss over a long‐term time horizon. Reactive N loss is ranked across 18 fertilizer management practices, which could assist farmers in weighing the tradeoffs between field trafficability, manure storage capacity, and expected N loss. Core Ideas: The impacts of climate variability were often greater than the impacts of fertilizer management. Fall‐applied manure resulted in more N loss than spring‐applied, primarily from N leaching. Lowest N loss occurred from split and sidedress urea at all three locations. More NH3 volatilization and N2 O losses occurred from organic fertilizer, but N leaching was similar. Similar fertilizer management recommendations can be made across all three locations.